PEPFAR Scale-up of Pediatric HIV Services: Innovations, Achievements, and Challenges - Abrams, Elaine J.; Simonds, R. J.; Modi, Surbhi; Rivadeneira, Emilia; Vaz, Paula; Kankasa, Chipepo; Tindyebwa, Denis; Phelps, B. Ryan; Bowsky, Sara; Teasdale, Chloe A.; Koumans, Emilia; Ruff, Andrea J. (Journal of acquired immune deficiency syndromes, 2012)
HIV/AIDS has had a profound impact on children around the world since the start of the epidemic. There are currently 3.4 million children under the age of 15 years living with HIV globally, and more than 450,000 children currently receiving lifesaving antiretroviral treatment. This article describes efforts supported by the President’s Emergency Plan for AIDS Relief (PEPFAR) to expand access to treatment for children living with HIV in high-burden countries. The article also highlights a series of case studies that illustrate the impact that the PEPFAR initiative has had on the pediatric HIV epidemic. Through its support of host governments and partner organizations, the PEPFAR initiative has expanded HIV testing and treatment for pregnant women to reduce vertical transmission of HIV, increased access to early infant diagnosis for HIV-exposed infants, improved training and resources for clinicians who provide pediatric care and antiretroviral treatment, and, through public–private partnerships with pharmaceutical manufacturers, helped increase the number of medications available for the treatment of HIV-infected children in resource-limited settings.
Keywords: PEPFAR; Pediatric; Treatment; HIV